2019
DOI: 10.1038/s41561-019-0452-1
|View full text |Cite
|
Sign up to set email alerts
|

Sharp 660-km discontinuity controlled by extremely narrow binary post-spinel transition

Abstract: The Earth's mantle is characterised by a sharp seismic discontinuity at a depth of 660-km that can provide insights into deep mantle processes. The discontinuity occurs over only 2km -or a pressure difference of 0.1 GPa -and is thought to result from the post-spinel transition, that is, the decomposition of the mineral ringwoodite to bridgmanite plus ferropericlase. Existing high-pressure-temperature experiments have lacked the pressure control required to test whether such sharpness is the result of isochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…7a, b ). One plausible conclusion is that on average a sharper 660-km discontinuity exists beneath this region in line with mineralogical prediction 29 , 30 , compared with the 410-km discontinuity. A consistent conclusion was also obtained through fitting the waveform of P410P and P660P in NCFs 17 , which agrees with Lawrence and Shearer 31 who suggest a ~3 times thicker 410-km discontinuity relative to the 660-km discontinuity.…”
Section: Resultssupporting
confidence: 75%
“…7a, b ). One plausible conclusion is that on average a sharper 660-km discontinuity exists beneath this region in line with mineralogical prediction 29 , 30 , compared with the 410-km discontinuity. A consistent conclusion was also obtained through fitting the waveform of P410P and P660P in NCFs 17 , which agrees with Lawrence and Shearer 31 who suggest a ~3 times thicker 410-km discontinuity relative to the 660-km discontinuity.…”
Section: Resultssupporting
confidence: 75%
“…The sharp 660-km discontinuity seen in this study is consistent with an early work by Castle and Creager (2000) and a recent work by Zhang M et al (2019), which suggest that the discontinuity is at most 10 km thick, and it is marginally consistent with a previous Sto-P conversion study that concluded the discontinuity is ≤5 km thick (Yamazaki and Hirahara, 1994). A sharp 660-km discontinuity resulting from the post-spinel transition was also revealed in a recent mineral physics experiment by Ishii et al (2019). The broadened 660-km discontinuity observed before (e.g., Wang BS and Niu FL, 2010;Li J et al, 2013) was explained by the multiple phase transitions associated with dissolution of the olivine and garnet components (Wang BS and Niu FL, 2010), whereas the sharp 660-km discontinuity observed in this study referred only to the phase change of the olivine component.…”
Section: Earth and Planetary Physicssupporting
confidence: 92%
“…The water‐bearing phase in a slab located in the MTZ are expected to consist of nominally anhydrous minerals (e.g., wadsleyite and ringwoodite) and dense hydrous magnesium silicates (DHMS, such as superhydrous Phase B or Phase D) (Ohtani et al, 2004). Once ringwoodite reaches the base of the MTZ, it decomposes into LM assemblage (e.g., Ishii et al, 2018; Ishii, Huang, et al, 2019; Ishii, Kojitani, & Akaogi, 2019; Litasov et al, 2005), which is expected to host only ≈1,000 ppm of water (Fu et al, 2019; Litasov et al, 2003). Due to the release of water around 660‐km depth, this decomposition most likely causes major slab dehydration (Schmandt et al, 2014).…”
Section: Potential Impact On the Thermal Structure Of Subducting Slabsmentioning
confidence: 99%